Influences of poly[(styrene) x-stat-(chloromethylstyrene) y]s additives on dewetting behaviors of polystyrene thin films: Effects of polar group ratio and film thickness - Suntree Sangjan (2018)
This contribution investigates the addition of poly(styrene-stat- chloromethylstyrene (ClMS))s as dewetting inhibitors of polystyrene (PS) thin films with thicknesses ranging from 12 to 38 nm. The ClMS ratios in the copolymers are 5, 25 and 45 mol%. Atomic force microscopy and optical microscopy are utilized to follow morphological changes of blended PS/copolymer films upon annealing above their glass transition temperatures. We have found that thermal stability of the PS films is greatly improved when a small amount of the copolymers is added into the system. The polar ClMS groups provide anchoring sites with the polar SiO x /Si substrate while the styrene segments favorably interact with the PS matrix. The effectiveness of the copolymers as dewetting inhibitors is also found to increase with mole ratio of ClMS group. While the stability of PS films is systematically improved upon addition of the highly substituted copolymers, using the copolymer with relatively low ratio of ClMS group could lead to the opposite result. This class of copolymers can be utilized for improving thermal stability of ultrathin PS films. The fundamental knowledge from this study is also important for designing or selecting structure of additives used to improve the stability of polymeric thin films. © 2012 Elsevier B.V. All rights reserved.